Perioperative and Anesthetic Adverse events in Thailand (PAAd Thai) incident reporting study: Anesthetic profiles and outcomes - Charuluxananan S. (2017)
Background: The Royal College of Anesthesiologists of Thailand initiated registry and reporting of anesthesia service incidents and outcomes in 2005. Objectives: The Perianesthetic Anesthetic Adverse Events in Thailand (PAAd Thai) study aimed to investigate patient, surgical, and anesthetic profiles, and suggest strategies for prevention of adverse events. Methods: A prospective descriptive study was conducted in 22 hospitals across Thailand. Each hospital was invited to report, on an anonymous basis, any perianesthetic adverse incident during 12 months (between January 1 and December 31, 2015). A standardized incident report form was completed to determine the type of incident, and where, when, how, and why it occurred using closed and open-ended questionnaires. Data regarding main anesthetic techniques were also reported monthly. Descriptive statistics were used. Results: For 333,219 cases, 2,206 incident reports with 3,028 critical incidents were reported. The incidents commonly occurred in male patients (52.0%), aged ≤10 y (13.0%) and ≥70 y (18.2%). The incidence of adverse events included cardiac arrest within 24 h (15.5:10,000), death (13.0:10,000), reintubation (11.1:10,000), esophageal intubation (8.5:10,000), difficult intubation (8.0:10,000), and malignant hyperthermia (1:200,000). General, cardiothoracic, neurological, and otorhinolaryngological surgical specialties posed a high risk of incidents. Operating and recovery rooms were common locations for incidents. Conclusion: In the past decade, there were dramatic reductions of perioperative cardiac arrests and difficult intubations. Common factors related to critical incidents were inexperience, emergency, inadequate preanesthetic evaluation, inappropriate decisions, lack of vigilance, and inexperienced assistants. Suggested corrective strategies are compliance with guidelines, additional training, and improvement of supervision and quality assurance.